2002
DOI: 10.1254/jjp.89.29
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Vasorelaxation Induced by Black Currant Concentrate in Rat Thoracic Aorta

Abstract: ABSTRACT-We investigated the effect of black currant (BC) concentrate on smooth muscle in rat thoracic aorta. BC concentrate dose-dependently relaxed the norepinephrine (0.1 mM)-precontracted aorta, and the response was abolished after endothelium removal. Both oxyhemoglobin (1 mM), a nitric oxide (NO) scavenger, and 1H-[1,2,4]oxadiazolo-[4,3-a]quinoxalin-1-one (ODQ, 0.5 mM), an inhibitor of guanylyl cyclase (GC), inhibited the relaxing effect of BC concentrate. N G -nitro-L-arginine methyl ester (L-NAME, 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 28 publications
1
38
0
3
Order By: Relevance
“…Results of in vitro studies with individual anthocyanidin compounds (sugar free molecules, anthocyanin aglycones) were contradictory, as only delphinidin, but not malvidin or cyanidin, caused endotheliumdependent relaxation of rat aortic rings. 22 The study by Nakamura et al 23 showed that four individual anthocyanin compounds, applied either alone or in combination, caused …”
Section: Discussionmentioning
confidence: 99%
“…Results of in vitro studies with individual anthocyanidin compounds (sugar free molecules, anthocyanin aglycones) were contradictory, as only delphinidin, but not malvidin or cyanidin, caused endotheliumdependent relaxation of rat aortic rings. 22 The study by Nakamura et al 23 showed that four individual anthocyanin compounds, applied either alone or in combination, caused …”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo aortic ring assays were performed in accordance with the previously described methods of Nakamura et al (24 ). Briefly, male Sprague-Dawley rats (180 -220 g) were killed and the thoracic aortas were then isolated and cut into rings.…”
Section: Ex Vivo Aortic Ring Experimentsmentioning
confidence: 99%
“…We further examined the role of the NO-cGMP pathway in mediating the effect of anthocyanins on vascular dilation in vitro by using a well-established rat aortic ring model (24 ). The relaxant effects of anthocyanins upon phenylephrine-precontracted aortic rings with a functional endothelium were found to be significantly augmented when the cumulative anthocyanin concentration reached 5 g/mL (P Ïœ 0.001; Fig.…”
Section: Vascular Relaxant Effects Of Anthocyanin In Vitromentioning
confidence: 99%
“…7,8) Lack of functional vascular endothelium was confirmed by the loss of relaxant response to 3 mM acetylcholine before the experiment began. 9) After the contraction had reached a stable plateau, cumulative concentrations of test compound were added.…”
Section: Establishment Of Concentration-contractile Response Curves Omentioning
confidence: 99%